Pengaruh Investasi, Kapasitas Produksi, Nilai Produksi dan Jumlah Unit Usaha pada Sektor Industri Terhadap Penyerapan Tenaga Kerja di Kabupaten Bulungan - Aslan Aslan (AKUNTABEL, 2017)
The purpose of this study was to determine How much influence the investment to the production capacity in the district of Bulungan, To know How much influence the production capacity of the production value in the district of Bulungan, To know How much influence the production value of the number of business units in the district of Bulungan, To know How large indirect effect of investment on employment in the industrial sector through the production capacity in the district of Bulungan, To know How big is the indirect effect of production capacity in the labor market in the industrial sector through the production value in the district of Bulungan, To know How much influence the indirect value production on employment in the industrial sector through a number of business units in the district of Bulungan. The results of the research are investments (X1) direct effect on employment (Y) of 0.667. Production Capacity (X2) direct effect on employment (Y) of -0.040. Value of Production (X3) direct effect on employment (Y) of -0.282. Total Business Unit (Y1) direct effect on employment (Y) of 0.957. Investments (X1) direct effect on employment in the industrial sector through the production capacity (X2) is 0,053. Production capacity (X2) direct effect on employment in the industrial sector through the production value (X3) of 0.395. The production value (X3) direct effect on employment in the industrial sector through a number of business units (X4) of 0.886.Keywords:  Investation, Product Capacity, Product Value, Number of Business Units, Employment Absorpt